2017
DOI: 10.12973/ejmste/77044
|View full text |Cite
|
Sign up to set email alerts
|

A Flipped Experience in Physics Education Using CLIL Methodology

Abstract: Physics' curricula of Italian Scientific High Schools in the last years have been enhanced by the introduction of Quantum Mechanics and Content and Language Integrated Learning (CLIL). Education monitoring reveals that last year's students are experiencing many issues in learning in their second language (L2) and advanced and counter-intuitive contents. Our experiment is aimed at understanding and then overcoming those problems using educational methodologies based on social aspects. Thanks to the Internet, a … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
8
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 20 publications
(11 citation statements)
references
References 10 publications
1
8
0
Order By: Relevance
“…The findings on the significance of peer-collaboration agree with the previous CLIL teacher research (Breidbach & Medina-Suárez, 2014;Capone et al, 2017;Hüttner et al, 2013;Massler, 2012) and importance of professional development education for teacher development (Goris, 2009).…”
Section: Discussionsupporting
confidence: 89%
“…The findings on the significance of peer-collaboration agree with the previous CLIL teacher research (Breidbach & Medina-Suárez, 2014;Capone et al, 2017;Hüttner et al, 2013;Massler, 2012) and importance of professional development education for teacher development (Goris, 2009).…”
Section: Discussionsupporting
confidence: 89%
“…The results are also in good agreement with other previous studies such as Cagande and Jugar (2018) in which they show that inverted classroom had a positive impact on students' understanding of kinematics graphs. Capone et al (2017) also reported the similar findings where they implemented inverted classroom in difficult topics of physics, i.e. quantum mechanics and results with students gain benefit through this approach.…”
Section: Discussionmentioning
confidence: 53%
“…Motivation among physics students will increase their preparation for class, support their reading skills and increase their emphasis on conceptual understanding instead of worrying the mathematical aspect of physics. Capone, Sorbo and Fiore (2017) also agreed that the use of an inverted classroom under challenging topics such as quantum mechanics is beneficial to students. By that, in this study, we used a mixed-method comparative study of two pre-university level physics classrooms: one of them inverted and the other is controlled by traditional lecture-homework classroom.…”
Section: Introduction and Literature Review Of Inverted Classroom In Phmentioning
confidence: 97%
“…In this study, it related to the use of technology in learning as both media or management system. Learning with a flipped classroom strategy has been widely researched and applied to improve critical thinking skills; as well as online learning [7], [8], [10].…”
Section: Discussionmentioning
confidence: 99%